Reports, returns and other papers printed by the Houses of Parliament of Great Britain and Ireland [electronic resource] : Bering Sea arbitration, British case - Great Britain. ([London : Her Majesty's Stationery Office, 1890)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 16007-16012. At head of title: Parliamentary papers. "Volume [2]". Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44